2018
DOI: 10.1111/ipd.12445
|View full text |Cite
|
Sign up to set email alerts
|

Gagging prevalence and its association with dental fear in 4‐12‐year‐old children in a dental setting

Abstract: Aim The aims were to determine the prevalence of gagging in children in the dental setting, detect any association between gagging and dental fear in that setting, and determine if the association varied by type of setting. Design A total of 734 children (4‐12 years old), seeking dental care either at a University paediatric dental clinic (UC) or at a private paediatric practice (PP), filled out the Greek version of the Gagging Assessment Scale (GAS, subjective assessment) and the Greek version of the Children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…This may result in a child with a high probability of gagging at the dentist through operant conditioning. 30 The literature findings on this subject associate more severe gagging with higher fear in adults. 15,19,29 However, there are only a few studies examining the relationship between dental fear and gagging in the pediatric population.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…This may result in a child with a high probability of gagging at the dentist through operant conditioning. 30 The literature findings on this subject associate more severe gagging with higher fear in adults. 15,19,29 However, there are only a few studies examining the relationship between dental fear and gagging in the pediatric population.…”
Section: Discussionmentioning
confidence: 97%
“…25 In the study of Katsouda et al in 2018, males were reported to experience more gagging than females in the pediatric age group, which is in line with our study findings. 30 Patients who experience gagging during dental treatments may develop a tendency to gag during their future dental experience as a result of the gagging experience being accompanied by dental stimuli (dentist, dental instruments). 5,15 Therefore, as a result of gagging during dental treatment, the fear of the dentist and dental treatment may develop in the pediatric patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Katsouda and colleagues 20 discovered a significant link in youngsters aged 4-12 between gagging and dental anxiety; however, due to the nature of the study, the authors were unable to determine that the two have a cause and effect relationship 16 . Distraction technique's effectiveness in medical settings and with pediatric patients is extensively demonstrated.…”
Section: Discussionmentioning
confidence: 94%